(untitled) (European Science Methodical Journal, 2024)
This article explores the significant role of advertising in mass media within Uzbekistan and English-speaking countries, examining its historical development, economic impact, cultural influence, and effects on consumer behavior. It highlights the differences in advertising approaches shaped by cultural contexts and market maturity, noting Uzbekistan’s transition to a more competitive market economy and the established advertising traditions in English-speaking nations. The piece also discusses current challenges faced by the advertising sectors in both contexts, such as regulatory issues in Uzbekistan and consumer fatigue in English-speaking countries, while speculating on future trends driven by technological advancements and changing consumer preferences.